A Bifactor Exploratory Structural Equation Modeling Representation of the Structure of the Decent Work Scale: Evidence from China. (February 2023) - Liu, Doudou; Lan, Yuanmei; Li, Chaoping; Xu, Yan; Yang, Jie
The present study investigates the psychometric properties of decent work utilizing the bifactor exploratory structural equation modeling (Bifactor-ESEM) approach. Using a sample of 701 Chinese employees who completed the multidimensional Decent Work Scale (DWS: Duffy et al., 2017), this study reveals the superiority of the Bifactor-ESEM representation of DWS compared to alternative representations of the data (ICM-CFA, Bifactor-CFA, and ESEM). Additionally, the results of measurement invariance in the MIMIC framework indicate the DWS is equivalent in various age and job tenure samples of participants. Finally, the results provide evidence for the criterion validity by confirming the importance of accounting for both the G-factor (representing the global level of decent work) and the S-factors (representing the specific level of decent work), which shows that specific types of decent work explained variance in covariates (i.e., work well-being, life well-being, engagement, and turnover intention) over and above the variance already explained by the G-factor.